Pengaruh model problem based learning dengan strategi konflik kognitif terhadap kemampuan pemecahan masalah - Dedi Saputra Siagian; Ellis Salsabila; Eti Dwi Wiraningsih (SAP (Susunan Artikel Pendidikan), 2025)
Problem-based learning (PBL) model and cognitive conflict strategy have an impact on mathematical problem-solving ability (MCE) and initial mathematical ability (EAC). Students' poor problem-solving ability and the need for a learning model that teaches students to think critically and analytically are the main issues in this study. A quasi-experimental design with a 2×2 factorial design was used. All students of junior high schools in grade VII in Palmerah District were the subjects of this study. Two groups consisted of samples: one group used PBL with cognitive conflict, and the other used direct learning. Data analysis was carried out using t-test and Two Way ANOVA. The results of the t-test showed a significant difference between the average MCE of students who learned using PBL compared to direct learning (t(142) = -2.539, p = 0.012). The results of the ANOVA test showed that KAM had a significant effect on KPM (F(1,92) = 453.358, p = 0.000), and there was an interaction between the learning model and KAM on KPM (F(1,92) = 11.043, p = 0.001). Thus, the PBL model with cognitive conflict strategy has proven to be effective in significantly improving students' mathematical problem solving abilities, especially when adjusted to the students' initial mathematical ability level